PELAYANAN KENAIKAN PANGKAT GURU SMA PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGAH - Masfah, Masfah; Pasinringi, Andi; Nurhannis, Nurhannis (Katalogis, 2020)
This study aims to find out and describe the High School Teacher Promotion Improvement Assessment Service at the Education and Culture Office of Central Sulawesi Province. The usefulness of this research is theoretical and practical. In the Literature Review explains the Concept of Service Quality, Public Services, Teacher Paradigm, Status and Position of Teachers, Requirements for making a Teacher, Tasks and Functions of Teachers, Teacher's Rights and Obligations, Teacher's Credit Numbers. Thinking of the theory of Zeithml, Parasuraman and Berry which includes Tangibles, Reability, Responsiveness, Assruance and Empathy. Research with qualitative methods, Research Locations in the Education and Culture Office of Central Sulawesi Province, Research Time for three months, Informants are ASN elements (State Civil Apparatus relating to Research), Operational definitions of concepts namely, Tangibles or direct evidence related to facilities and Infrastructure that is still lacking due to earthquake damage and Reability or reliability indicators related to the problem of discipline of existing employees does not arrive on time, while the Responseviness, Assurance and Empathy Indicators are good enough. Thus, it can be concluded that the quality of service promotion for teachers at the Central Sulawesi Proinsi Education and Culture Office is good.